PERAN KEPUASAN DALAM MEMEDIASI PENGARUH KOMUNITAS MEREK TERHADAP LOYALITAS PENGGUNA HARLEY-DAVIDSON DI KOTA DENPASAR - Panasea, I Gede Nandya Oktora; Suprapti, Ni Wayan Sri (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 2 Tahun 2013)
This study empirically explores the influences of brand community on loyalty when mediated by satisfaction. The data on this research were collected from observation, interviews, and  questionnaires.Data analysis methods that used on this research were descriptive and inferential statistics. Descriptive statistics such as frequency distributions were used to describes the  characteristics of the respondents, while inferential statistics such  as  Baron  and  Kenny  Steps  and  Sobel  test  is  used  to  test  the  hypotheses.  The  results  showed  that satisfaction partially mediates the effect of brand community on loyalty of Harley-Davidson users inDenpasar. It shows that satisfaction is an essential element for the brand community to realize the brand loya lty.
Keywords: brand community, satisfaction, loyalty